Distribution of Macrozoobenthos as a Bioindicator of Water Quality at Tanjung Peni Beach, Citangkil District, Cilegon City - Nadia, Putri; Nurdin, Hery Sutrawan; Aryani, Desy (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Cilegon City has several rivers, one of which empties into Tanjung Peni Beach, the location is behind the Cilegon Estate Industrial Estate. There are changes in water quality due to several anthropogenic activities around coastal areas, so that they affect organisms, especially macrozoobenthos. This study aims to analyze the distribution of macrozoobenthos and analyze the status of water quality conditions. The research was conducted in March-May 2024 at Tanjung Peni Beach, Citangkil District, Cilegon City using a purposive sampling method consisting of 3 observation stations. There are several data analyses, namely abundance, diversity, uniformity, dominance, morisita, sediment texture and Family Biotic Index (FBI). The macrozoobenthos obtained consisted of 34 species from 3 classes, namely gastropods (29 species), bivalves (1 species) and malacostraca (4 species). The distribution of macrozoobenthos obtained is diverse and grouped with the texture of sand sediments and clay clay. Based on the calculations of the three stations, the diversity value is medium, the uniformity value is small and high, and the dominance value is low and medium. Based on FBI calculations, the water quality condition at Tanjung Peni Beach is at station 1 at 6,057 (somewhat poor), station 2 at 6,091 (somewhat poor) and station 3 at 5,694 (moderate).